Investigation of Calcium Forms in Lichens from Travertine Sites - Dajana Ručová; Tamara Đorđević; Matej Baláž; Marieluise Weidinger; Ingeborg Lang; Andrej Gajdoš; Michal Goga (Plants, 2022)
Lichens are symbiotic organisms with an extraordinary capability to colonise areas of extreme climate and heavily contaminated sites, such as metal-rich habitats. Lichens have developed several mechanisms to overcome the toxicity of metals, including the ability to bind metal cations to extracellular sites of symbiotic partners and to subsequently form oxalates. Calcium is an essential alkaline earth element that is important in various cell processes. Calcium can serve as a metal ligand but can be toxic at elevated concentrations. This study investigated calcium-rich and calcium-poor sites and the lichen species that inhabit them (Cladonia sp.). The calcium content of these lichen species were analyzed, along with localized calcium oxalate formed in thalli collected from each site. The highest concentration of calcium was found in the lichen squamules, which can serve as a final deposit for detoxification. Interestingly, the highest content of calcium in Cladonia furcata was localized to the upper part of the thallus, which is the youngest. The produced calcium oxalates were species-specific. Whewellite (CaC2O4∙H2O) was formed in the case of C. furcata and weddellite (CaC2O4∙2H2O) was identified in C. foliacea.